Publishing Translated Books for Young Readers in Australia - de Vicente Capua, M.C.; Henningsgaard, Per (2021)
This article examines the various factors (beyond simply the perceived cultural and economic value) that influence a book being selected for translation and publication in the English language. More specifically, this article asks, “What influences the prospects of a book for young readers being published in translation in Australia?” Using a combination of literature review, the collection of publication data about translated books for young readers, and interviews with industry professionals, it was determined that there are three factors that influence a book being selected for translation and publication. These factors are the global language hierarchy, narrative structures and relationships.